GLOBAL DIGITAL TAXES IN INTERNATIONAL TRADE AND ITS URGENCE FOR INDONESIA - Rivaldi, Regi (Department of Transnational Business Law, Faculty of Law Universitas Padjadjaran, 2021)
Members of the Organization for Economic Cooperation and Development (OECD) and World Trade Organization are working together to exploring issues related to digital service product tax policies. The ability of digital companies that operate without the need to be physically present has sparked debates in international forums regarding the allocation of rights and tax rights reallocation agreements or nexus. Not to mention the physical absence of digital companies that makes jurisdictional constraints for State that want to collect taxes from digital companies. The scope of digital services makes it difficult for policy makers to define what digital service products are. This problem has led initiate international forums to reforms international tax regulations that are able to accommodate these interests. TOECD formed a Task Force Digital Economy to respond this problem and at the same time identify issues that are related to digital service product taxes to make it relevant.